Transformasi Informasi Digital untuk Pelayanan Publik dan Pembangunan Daerah Tertinggal: Studi Strategis atas Peran Diskominfo Kabupaten Maluku Tenggara - Kilmanun, Febyyola Welmina; Telussa, Sandra Ivonnie (Universitas Pattimura, 2025)
This article examines the strategic role of the Communication and Information Office (Diskominfo) of Southeast Maluku Regency in driving digital information transformation to support public service delivery and regional development in underdeveloped areas. The study aims to explore how Diskominfo manages and disseminates public information effectively, particularly in regions with limited internet access and low literacy levels. Using a qualitative descriptive approach and case study method, data were collected through observation, in-depth interviews, and document analysis. The findings reveal that Diskominfo implements multiple strategies, including the use of social media, digital platforms, and subscription-based radio and television broadcasts. The office has also developed seven digital-based public service applications and conducts a systematic information management process—ranging from collection and verification to distribution—guided by journalistic accuracy principles. Despite these efforts, significant challenges persist, such as telecommunication blank spots, infrastructure limitations, and low public awareness of government information. This study contributes novel insights by mapping adaptive digital strategies tailored to the geographical and social context of disadvantaged regions. It concludes by highlighting the need to strengthen human resource capacity, expand information technology infrastructure, and fully implement electronic public service systems. The recommendations are relevant to advancing social sciences and humanities, particularly in the domain of inclusive digital governance and regional development.